A review on the employment of the hydraulic cylinder for lifting purposes - Istabraq Hadi Abed Al-Hady; Farag Mahel Mohammed; Jamal Abdul-Kareem Mohammed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The hydraulic elevator is both a cost-effective system and results in extremely clean building exterior lines since the usual penthouse-type machine room is eliminated. Without the need for wires, counterweights, or pulleys, this elevator can transfer people between levels. One of the most significant factors to consider when designing people's elevators is that they should not be disturbed when going between levels and that the elevators should stop accurately. As a consequence, innovative technologies such as the electro-hydraulic servo system (EHSS) may be employed with a traditional hydraulic elevator. This technology may employ speed and position input to provide the desired degrees of speed control, riding comfort, and leveling precision. The EHSS is a closed-loop control system that operates as a drive unit, raising and lowering the elevator cabin in response to a variable like position, velocity, or force. This paper examines various types of hydraulic systems for lifting purposes, as well as the application of servo system principles to hydraulic control valves, to credibly provide the traditional hydraulic elevator with a selectable diversity of precise and smooth transport characteristics across floors. This study also looks at how elevators employ telescopic hydraulic cylinders efficiently for lift purposes in the elevator.